AUDIT KEPATUHAN OLEH QUALITY MANAGEMENT SYSTEM PADA STANDAR OPERASIONAL PROSEDUR QUALITY CONTROL DEPARTMENT PT.SAGATRADE MURNI - Adisthy Shabrina Nurqamarani3, Rudi Hastomo Imam Nazarudin Latif2 (EKONOMIA, 2021)
This study discusses about compliance rate based on  ISO 9001:2015 on performance of Quality Control Department at  PT. Sagatrade Murni in handling non conformities product and improvement steps in product that are non conformities in manufacturing process. This study used a comparative method by comparing the occurrence in field with ISO 9001:2015. The theory used in this research is audit. The hypothesis proposed is  Quality Control Department has implemented procedure in accordance with Quality Management System ( ISO 9001:2015 ). Analytical tools used in this research is ISO 9001:2015 and the method is comparative method, which is a method that compare between procedure used in field with ISO 9001:2015 at PT. Sagatrade Murni. The result show that Quality Control has implemented ISO 9001:2015, but some audit findings  documents is not storage well. The conclusion of this study is application of  procedure in Quality Control already in accordance with ISO 9001:2015 so hyphotesis is accepted.